2022
DOI: 10.3389/fphar.2022.940716
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of STING/TBK1 Signaling Attenuates Myeloid Fibroblast Activation and Macrophage to Myofibroblast Transition in Renal Fibrosis

Abstract: Renal fibrosis is an important pathological biomarker of chronic kidney disease (CKD). Stimulator of interferon genes/TANK binding kinase 1 (STING/TBK1) axis has been identified as the main regulator of innate immune response and closely related to fibrotic disorder. However, the role of STING/TBK1 signaling pathway in kidney fibrosis is still unknown. In this study, we investigated the effect of pharmacological inhibition of STING/TBK1 signaling on renal fibrosis induced by folic acid (FA). In mice, TBK1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Furthermore, the role of the STING pathway in liver, kidney and lung fibrosis has also been demonstrated [143][144][145]. Conversely, drug inhibition of STING/TBK1 signaling has been shown to reduce the conversion of bone marrow fibroblasts and macrophages into myofibroblasts [146], thus presenting is a promising pathway for targeted fibrosis therapy. Ferroptosis is a type of cell death that is dependent on iron and causes oxidative DNA damage.…”
Section: Cgas/sting Pathway-identifier Of Dna Damagementioning
confidence: 99%
“…Furthermore, the role of the STING pathway in liver, kidney and lung fibrosis has also been demonstrated [143][144][145]. Conversely, drug inhibition of STING/TBK1 signaling has been shown to reduce the conversion of bone marrow fibroblasts and macrophages into myofibroblasts [146], thus presenting is a promising pathway for targeted fibrosis therapy. Ferroptosis is a type of cell death that is dependent on iron and causes oxidative DNA damage.…”
Section: Cgas/sting Pathway-identifier Of Dna Damagementioning
confidence: 99%
“…RU.521 has been used to improve disease outcomes in rodent models of neuroinflammation caused by subarachnoid hemorrhage and cerebral venous sinus thrombosis, colitis, sepsis-induced organ injury, , acetaminophen-induced liver injury, acute lung injury, hypertensive heart injury, ischemic injury in the lung and neonatal brain, femoral fracture healing, and aging-related endothelial dysfunction . Additionally, administration of H-151 has improved outcomes in rodent models of acute kidney injury (AKI), renal fibrosis, amyotrophic lateral sclerosis (ALS), sepsis-induced organ injury, , psoriasis, ischemia-reperfusion injury in the intestine, myocardial infarction, LPS-induced acute lung injury, , Alzheimer’s, and neuropathic pain resulting from chronic constriction injury . However, early experiences with these molecules has also identified several potential pharmacological barriers that may inhibit the translation of RU.521 and H-151 (and potentially cGAS/STING inhibitors more generally).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several studies have discovered that the cGAS-STING pathway not only serves a protective role in combating foreign pathogens but also plays a signi cant role in the initiation and progression of various conditions such as infections, in ammation, tumors, autoimmune diseases, and other diseases [11] . Moreover, there have been reports indicating the involvement of the STING pathway in the pathogenesis of brotic diseases, including pulmonary brosis, liver brosis, and renal brosis [12][13][14] . It has been demonstrated that STING is highly expressed on hematopoietic cells, such as macrophages [15] and the presence of macrophages is essential for the proper healing of wounds.…”
Section: Introductionmentioning
confidence: 99%